Temporal Changes in the Quality of Acute Stroke Care in Five National Audits across Europe. (9th December 2015) - Hillmann, Steffi; Wiedmann, Silke; Fraser, Alec; Baeza, Juan; Rudd, Anthony; Norrving, Bo; Asplund, Kjell; Niewada, Maciej; Dennis, Martin; Hermanek, Peter; Wolfe, Charles D. A.; Heuschmann, Peter U.
Abstract : Background. Data on potential variations in delivery of appropriate stroke care over time are scarce. We investigated temporal changes in the quality of acute hospital stroke care across five national audits in Europe over a period of six years. Methods. Data were derived from national stroke audits in Germany, Poland, Scotland, Sweden, and England/Wales/Northern Ireland participating within the European Implementation Score (EIS) collaboration. Temporal changes in predefined quality indicators with comparable information between the audits were investigated. Multivariable logistic regression analyses were performed to estimate adherence to quality indicators over time. Results. Between 2004 and 2009, individual data from 542, 112 patients treated in 538 centers participating continuously over the study period were included. In most audits, the proportions of patients who were treated on a SU, were screened for dysphagia, and received thrombolytic treatment increased over time and ranged from 2-fold to almost 4-fold increase in patients receiving thrombolytic therapy in 2009 compared to 2004. Conclusions. A general trend towards a better quality of stroke care defined by standardized quality indicators was observed over time. The association between introducing a specific measure and higher adherence over time might indicate that monitoring of stroke care performance contributes to improving quality of care.